This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using complex number multiplication:
( 2 − 1 + i 3 ) 3 = 2 3 ( − 1 + i 3 ) 3 = 8 1 ( − 1 + i 3 ) 3 = 8 1 ( − 1 + i 3 ) ( − 1 + i 3 ) ( − 1 + i 3 ) = 8 1 ( 1 − 2 i 3 − 3 ) ( − 1 + i 3 ) = 8 1 ( − 2 − 2 i 3 ) ( − 1 + i 3 ) = 8 1 ( 2 − 2 i 3 + 2 i 3 + 6 ) = 8 1 ( 8 ) = 1
This is clearly the cube root of unity. In maths use some rememberence as well so as to svore high in JEE type exams.
( 2 − 1 + i 3 ) correspondes to 2 4 0 ° 2/3 of a full circle. Potentiating a complex number behaves as addition on the angles, leading ( 2 − 1 + i 3 ) 3 corresponding to 7 2 0 ° = 3 6 0 ° = 0 ° with cos ( 0 ) = 1 given the desired answer. For less text, more math and more accurrancy consider reading Rishabh Cool answer.
A few things that need revision in this solution: 1) The complex number in question corresponds to a point with an argument of 1 2 0 ∘ in the complex plane, and a magnitude of 1. It is 1/3 of a unit circle. 2) Exponentiation of a complex number results in a MULTIPLICATION of the argument by the exponent ( a consequence of repeated addition by the same number ) and exponentiation of the magnitude of the complex number. Therefore, setting the complex number in question equal to z , we have that z 3 = 1 3 cos 2 π = 1 .
Problem Loading...
Note Loading...
Set Loading...
cos ( 3 2 π ) = − 1 / 2 , sin ( 3 2 π ) = 3 / 2
Therefore given expression using Euler's form can be written as:
( cos ( 3 2 π ) + i sin ( 3 2 π ) ) 3 = ( e 3 2 π i ) 3 = e 2 π i = cos ( 2 π ) + i sin ( 2 π ) = 1